Construction and preliminary test of a geothermal ORC system using geothermal resource from abandoned oil wells in the Huabei oilfield of China. (1st December 2017) - Yang, Yi; Huo, Yaowu; Xia, Wenkai; Wang, Xurong; Zhao, Pan; Dai, Yiping
Abstract: In this study, a low-temperature geothermal organic Rankine cycle (ORC) system was designed to generate electric power using geothermal resource from abandoned oil wells in the Huabei oilfield of China. Several main sections were constructed including the geothermal water cycle, intermediate water cycle, ORC, cooling water cycle, lubricant oil cycle, bypass and control systems. Using R245fa as the working fluid, a four-stage axial turbine was specially designed and manufactured, to drive a grid-connected alternator. An onsite preliminary test was conducted in the oilfield and part of the experimental data were presented and analyzed. The turbine isentropic efficiency and ORC efficiency were evaluated. Besides, an intermediate cycle efficiency was proposed to show the influence of the heat loss of the intermediate water cycle on the system performance. Experimental results showed that a turbine efficiency of 78.52% and an ORC efficiency of 5.33% could be obtained. The average of intermediate cycle efficiency was 77.98%, indicating that the heat loss of the intermediate water cycle was considerable and should not be ignored. The construction and preliminary test of this ORC system could provide some meaningful references for the researchers and engineers to establish desirable geothermal ORC power plants using abandoned oil wells. Highlights: Geothermal resources from abandoned oil wells were utilized for power generation. An intermediate water cycle was proposed to avoid the blockage problem. A specially designed four-stage axial turbine was applied to the system. The turbine performed well and could be generalized for geothermal ORC system. The proposed system could be a desirable option for geothermal energy applications.